Synthesis, structural and magnetic characterization of spherical high entropy alloy CoCuFeNi particles by hydrogen reduction assisted ultrasonic spray pyrolysis - Kucukelyas, Burak; Safaltin, Serzat; Sam, Ebru Devrim; Gurmen, Sebahattin (Walter De Gruyter Gmbh, 2022)
The present study focuses on the synthesis, structural and magnetic characterization of CoCuFeNi high entropy alloy particles. The hydrogen reduction assisted ultrasonic spray pyrolysis method was used to synthesize nanocrystalline quaternary CoCuFeNi particles in a single step. The effect of synthesis temperature on the structure, morphology and the size of particles was investigated. The syntheses were performed at 700 degrees C, 800 degrees C, and 900 degrees C with 0.1 M concentration of metal nitrate salts precursor solution. The structure and morphology of products were characterized through X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy and vibrating sample magnetometer studies. Diffraction pattern based calculations revealed that crystallite sizes of CoCuFeNi particles were in the range of 15.6-26.7 nm. Scanning electron microscopy and energy dispersive spectroscopy investigations showed that particles were agglomerated from crystallites and in spherical morphology with equiatomic elemental composition. According to vibrating sample magnetometry results, soft magnetic properties were observed for CoCuFeNi particles. X-ray photoelectron spectroscopy results showed that the surface has a thin layer of copper oxide.
Keywords: CoCuFeNi particles; High entropy alloys; Hydrogen reduction; Magnetic materials; Ultrasonic spray pyrolysis